Learning at your fingertips. Issue 2 (1st September 2011) - Scott, Ros
Abstract : Introduction: CHAS is Scotland's only children's hospice organisation and has three hospice services: Rachel House in Kinross, Robin House in Balloch, and CHAS at Home which operates from both hospices and has a small base in Inverness. With 235 staff across 11 sites and 900 volunteers throughout Scotland, access to consistent high quality learning opportunities can be a challenge, regardless of role. Aims: The aim of the project was initially to meet our statutory/mandatory training needs and to develop a structured and accessible blended learning approach. One key component of this was the development of online learning modules for all statutory/mandatory areas. Methods: Research was undertaken to find the best platform for CHAS to use which would be easy to create and upload module materials, and straightforward for staff and volunteers to use. It was also important for the learning to be validated through short assessments. Results: Initially eight modules were developed and rolled out to all staff, including topics such as Fire Safety, Infection Control, Moving and Handling Objects and Display Screen Regulations. After initial apprehension staff quickly began to see the benefits and some even described the process as 'addictive'! Staff began to see the possibilities for supporting other professional learning through on-line learning, and have prepared new modules. Conclusion: The results of our work with online learning far surpassed our initial expectations. Staff are really engaged with the process both of completing modules and with many new ideas for topics. It has also encouraged greater use of electronic communication in CHAS. Currently there are 14 modules available to staff: topics as Lone Working and Bereavement have been added. We are also about to begin the process of rolling out statutory/mandatory modules to volunteers.